2015
DOI: 10.23938/assn.0050
|View full text |Cite
|
Sign up to set email alerts
|

Trends and social inequalities in cervical cancer and breast cancer screening in Madrid: Non-Commumicable Disease Risk FactorSurveillance System (SIVFRENT-A) from 1995 to 2010

Abstract: All groups increase in preventative behaviors and those who did not, had a high prevalence from the start.Itis worth mentioning the stagnation of mammography in disadvantaged women in the period 2007-2010. There was a social gradient for preventive preventative measures, which was lower in the population-basedscreening (mammography) than in the opportunistic one (cytology).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Economic status showed the greatest contribution to inequality in gynecological, cervical smear, and breast examination rates. The elevation in economic status increased the pro-rich inequality in health examination service utilization and was consistent with the findings of other recent international studies [ 20 , 22 , 23 ]. Enhanced economic status increases health needs and health examination service utilization, and women with higher economic levels are more likely to take the initiative to access women's health examination services [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Economic status showed the greatest contribution to inequality in gynecological, cervical smear, and breast examination rates. The elevation in economic status increased the pro-rich inequality in health examination service utilization and was consistent with the findings of other recent international studies [ 20 , 22 , 23 ]. Enhanced economic status increases health needs and health examination service utilization, and women with higher economic levels are more likely to take the initiative to access women's health examination services [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported inequity in the utilization of health examination services via regression analysis [ 21 , 22 ], relative index [ 23 ], or slope index [ 24 ], but few studies have measured inequity via the concentration index and decomposition of the concentration index. Therefore, selected key indicators were used in this study to examine equity in health examination service utilization by women from underdeveloped areas in the western region of China.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few publications that discuss issues of inequality in relation to the implementation of preventive practices based on regional characteristics [26]. …”
Section: Discussionmentioning
confidence: 99%